Assessing physical activity through questionnaires – A consensus of best practices and future directions. (September 2020) - Nigg, Claudio R.; Fuchs, Reinhard; Gerber, Markus; Jekauc, Darko; Koch, Theresa; Krell-Roesch, Janina; Lippke, Sonia; Mnich, Carina; Novak, Bernhard; Ju, Qianqian; Sattler, Matteo C.; Schmidt, Steffen C.E.; et al.
Abstract: Questionnaires to assess physical activity (PA) have served and continue to serve important purposes in both research and practical application as they capture the self-reported aggregation of the individual which is at times complemented with device-based measures. This paper presents an expert consensus on best practices and future directions regarding the use of PA questionnaires (PAQ). The expert panel discussions that informed this manuscript took place during the 2nd International Workshop of the Center for the Assessment of Physical Activity (CAPA), held in Karlsruhe, Germany in July of 2019. Practically, we recommend to identify already existing and published PAQs in order to address a specific research question. To facilitate this, a decision framework (decision guide aide) for selecting a PAQ, consisting of purpose, construct, measurement unit, recall period, population, setting, measurement quality, feasibility/ease of use, and resources is presented. These best practices are discussed to provide some standardization for the field. With regard to future research on PAQs, continued efforts to improve validity, reliability, and sensitivity to change; consider the recall period; incorporate information on or adapt for a specific cultural/ethnic/environmental context; and strategically combine PAQ with other PA assessment methods capitalizing on the advancement of technology, are needed. These recommended future directions are outlined in order to motivate and challenge researchers to continually improve the field of PAQ research. Highlights: Best practices include identifying already existing and published PAQs in order to address a specific research question. To help select an existing PAQ a decision framework is presented consisting of purpose, construct, measurement unit, recall period, population, setting, measurement quality, feasibility/ease of use, and resources is presented. Future PAQ research directions include continued efforts to improve validity, reliability, and sensitivity to change; consider the recall period; incorporate information on or adapt for a specific cultural/ethnic/environmental context; and strategically combine PAQ with other PA assessment methods capitalizing on the advancement of technology, are needed.